Innesto di cellule mesenchimali su membrana nel trattamento delle patologie cartilaginee della tibio-tarsica - Cortese, F.; Puddu, L.; Mercurio, D.; Santandrea, A. (Lo Scalpello - Journal, 2019)
TREATMENT OF ANKLE CHONDRAL LESIONS WITH MESENCHYMAL STEM CELLS IMPLANT ON COLLAGEN MEMBRANE Osteochondral lesions of the ankle are very common, the talus being the second most frequent site after the knee, and their treatment depends on the lesion site, width and depth. According to the Giannini classification as lesion type II (width larger than 1.5 cm2 and depth lower than 15 mm), the suggested treatment is through mesenchymal stem cell implant on collagen membrane. The surgical technique consists in arthroscopic assessment of the lesion, mesenchymal stem cell harvesting from the iliac crest, processing of the cells on the lesion site and implant on collagen membrane (IOR G1 technique), which may be performed arthroscopically or through the mini-open technique. The authors report their experience with this procedure on 36 cases over four years. All patients have been evaluated pre- and postoperatively using the AOFAS and VAS scales. MRI was performed preoperatively and at 6, 12 and 24 months postoperatively, using T1 and T2-weighted FSE sequences. Eighteen cases were evaluated with a minimum follow-up of 24 months both clinically and throughMRI; in three cases, an arthroscopic second look was performed. In all cases, AOFAS and VAS scores improved significantly, MRI scans showed filling of chondral defects in 83% of cases at 24-month follow-up, although in 30% of MRI scans subchondral bone hyperintensity was still present. In spite of these findings, the technique proved to be effective in improving the clinical and radiological outcomes in most cases.